Complementary and Integrative Medicine Use: A National Survey - Christophe Raspaud; Laurence Culine; Joanne Velazquez; Gregory Ninot; Nicolas Molinari; Ingrid Portilla (Integrative Medicine Reports)
Objective: This large-scale survey aimed to investigate the use of Complementary and Integrative Medicine (CIM) across France. Design: Observation multicentric study. Setting: This survey study was conducted from October 10, 2022 to October 28, 2022 in medical, surgical, and obstetric clinics across France. Self-administered questionnaires specifically designed for the study were used to collect data related to subjects’ prior use of CIM (type of therapy used, reasons for use, cost, duration, who recommended the therapy) and patient demographic data. The questionnaires were made available at the admissions office, secretary’s office, or waiting rooms of clinics. Results: A total of 1178 questionnaires collected in 26 multipurpose clinics were analyzed. Two-thirds of patients (65%) reported having used at least one CIM, with a mean of four therapies used per patient. Osteopathy, massage, homeopathy, acupuncture, and psychotherapy were the most frequently reported therapies. More women than men declared using these therapies, and users were significantly younger than nonusers. Therapies were used for a variety of health conditions, but were most commonly used to treat pain (32%), anxiety (11%), cancer (9%), well-being (8%), and stress (7%). Patients mainly discussed use with family members (53%), doctors (52%), and/or partners (45%). Friends (29%), doctors (26%), or family members (18%) most commonly recommended therapies. Patients estimated spending a median of €330 over a median duration of 24 months. Depending on the therapy, 71%–92% of patients would recommend CIM to others. Conclusions: A substantial number of patients seen in French multipurpose clinics, particularly female and young adults, report using CIM. Patients have a positive opinion of these therapies, report using them long term, and devote a significant budget to them.